1990
DOI: 10.1084/jem.172.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate can function as a cell adhesion molecule and CD44 participates in hyaluronate recognition.

Abstract: SummaryA cell adhesion model was previously used to select a series of monoclonal antibodies (mAbs), which were subsequently found to recognize CD44/Pgp-1 . Interest in these reagents increased with the finding that they totally inhibited production of lymphoid or myeloid cells in long-term bone marrow cultures. Further investigation has now revealed that hyaluronate is a potential ligand for CD44 and that hyaluronate recognition accounts for the adhesion between B lineage hybridoma and stromal cells . The hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
278
2
6

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 586 publications
(294 citation statements)
references
References 35 publications
8
278
2
6
Order By: Relevance
“…It is the principal cell surface receptor for hyaluronate [35], [36] which is widely distributed in extracellular matrices and present within the extracellular matrix of the cumulus cell-oocyte complex [37]. While successful implantation and embryonic development can occur in its absence [38], notwithstanding, it is implicated in a number of biological phenomena, including cell-cell adhesion, migration, embryonic development and pathogenesis [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is the principal cell surface receptor for hyaluronate [35], [36] which is widely distributed in extracellular matrices and present within the extracellular matrix of the cumulus cell-oocyte complex [37]. While successful implantation and embryonic development can occur in its absence [38], notwithstanding, it is implicated in a number of biological phenomena, including cell-cell adhesion, migration, embryonic development and pathogenesis [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 exhibits affinity to HYA on lymphocytes and could account for adhesion between lymphocytes of B lineage and stromal cells [24,25]. It mediates the HYA-binding of human myeloid KG1 and KG1 A cells [26].…”
Section: Macromolecular and Cellular Interactionsmentioning
confidence: 99%
“…As noted above, this binding site was later defined as CD44, which is responsible for the adhesion of HYA to endothelial cells [22] and human myeloid cell lines [26], and for the adhesion of B-lineage lymphocytes to stroma cells [25]. CD44 can be distinguished in two forms, one epithelial and the other haemopoietic, with different adhesion potentials for HYA-bearing cells [27,28].…”
Section: Adhesionmentioning
confidence: 99%
“…Comparison of cell-cell contact and cell-cell noncontact culture systems for B cell development It has been reported that cell-cell interactions between stroma and progenitor cells play important roles in early Blymphopoiesis in both murine 11,[27][28][29][30][31] and human [32][33][34][35] systems. Therefore, to elucidate whether cell-cell interactions between MS-5 cells and progenitor cells are required for the generation of CD19 + cells in our culture, CD34 + cells were cultured with or without the 0.45 m microporous filter on an MS-5 cell layer.…”
Section: Figurementioning
confidence: 99%